IMPORTANCE SOCIO-ECONOMIQUE DE PTEROCARPUS ERINACEUS POIR. AU TOGO - Segla, Kossi Novinyo; Adjonou, Kossi; Radji, Abdou Raoufou; Kokutse, Adzo Dzifa; Kokou, Kouami; Habou, Rabiou; Kamana, Pouwisawe; Bationo, Babou AndrÃ©; Mahamane, Ali (European Scientific Journal, ESJ, 2015)
Pterocarpus erinaceus Poir. (Fabaceae) is an spontaneous, highly exploited and threatened plant species to guineo-sudanese and sudanosahelian regions in Togo. This study examines the level of knowledge of the species, the different uses of the species in order to assess the impacts of human activities on the development of that resource. To achieve these objectives, the methodological approach was to collect quantitative and qualitative data on a sample of 2339 respondents. Three different types of questionnaires, an interview guide and an observation grid were used as data collection tools. The results show that the species is very well known by 100% of respondents of different socio-professional and socio-linguistic groups. Approximately 46 uses distributed in 8 use categories have been identified by the different socio-cultural and socio-professional groups. Close to 33 evils are healed by the organs of P. erinaceus.The results also showed that the wood of P. erinaceus is exported as finished parquet, pallets and Bastings. Between 2011 and 2012, the Togo exported respectively 18 8064 units or 70 m3, 10 5038 units or 9440 m3, 59 86 970 unit or 70 m3 and 239 m3 or 10 units of these products. Severe forms of exploitation have contributed to amplify the effects of human action on the degradation of the resource. The different uses of the species therefore testify to the urgency and the need for the implementation management plans of areas colonized by P. erinaceus for the conservation of the species.